Analysis of the Role of the Covid Officer Unit in Company Organizations - Rahadi, Dedi Rianto; Dewantara, I Putu Nara Krisna (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2022)
This study aims to analyze the role of the Covid-19 task force in corporate organizations. This research is qualitative. The Data collection tools used were direct observation and documentation study. Result: research related to COVID-19 officer unit Appointment Decree No. 142/SII/HO/ADM/IX/2020 which appointed 21 employees with 1 chairman, 1 deputy chairman, 1 public relation and legal officer, 2 regional coordinators, 3 secretaries, and 16 sub-coordinators. Furthermore, the review results of Circular 065/SIT-HO/ADM/II/2020, each Department at PT Sankyu Indonesia International are advised to take all actions such as (1) Preparing thermometer gun at entrance to the building and worksite. (2) To prevent as much as possible, the entry of visitors to the office/workplace. (3) Meetings are conducted via video conference. (4) Avoiding unnecessary official travel; (5) Carryout important correspondence via official email (6) Serve delivery and reception by couriers at the entrance of office buildings (7) Ensure proper cleaning (8) Ensure supplies of hand sanitizer, soap, and water run in the bathroom. (9) Employees are advised to maintain their health (10) People who have the authority to give leave are advised to give leave whenever there is a request for self-quarantine as a precaution; and (11) Advise employees who are at higher risk, namely older employees, pregnant women and employees with underlying medical conditions, to take extra precautions